Autologous versus prosthetic nasal and auricular reconstruction – patient, professional and layperson perceptions. Issue 10 (October 2020) - Dings, J.P.J.; Vijverberg, M.A.; Hol, M.K.S.; Ulrich, D.J.O.; de Haan, A.F.J.; Verhage-Damen, G.W.; de Clonie Maclennan-Naphausen, M.T.P.; Kruyt, I.J.; Ghaeminia, H.; Bruekers-Schipper, G.B.; Ingels, K.J.A.O.; Dicker, G.J.; et al.
Abstract: The aim of this study was to retrospectively evaluate the perceptions of aesthetic outcome following the autologous and prosthetic reconstruction of nasal and auricular defects among patients, professionals (oral and maxillofacial surgeons and ear, nose and throat surgeons) and people unfamiliar with reconstructive surgery. The influence of anatomical subunits on the overall perception of nasal and auricular reconstructions was also determined. A total of 119 patients treated for nasal and auricular defects between 1997 and 2016, with a minimum follow-up period of 6 months, were selected, and photographs of 77 of these patients (65%) were presented in a digital survey and reviewed using a standardized questionnaire. No clinically relevant correlations were found between the age or gender of patients (as well as those of the respondents) and their scores. Prosthetic reconstructions of nasal and auricular defects were considered advantageous over autologous reconstructions in terms of the subjective aesthetic outcome in the view of the professionals, in particular oral and maxillofacial surgeons; however, the patients judged both techniques to be equally effective in terms of aesthetics. No anatomical subunits were found to have a significant impact on the overall match of a nasal or auricular reconstruction with the patient's face.